Research of titration curves of red mud samples - Váradi, Renáta; Székely, István (International Journal of Engineering and Management Sciences, 2019)
The aluminium demand is increasing worldwide, so the amount of red mud, which produced during the production of aluminium, is constantly increasing, also. The researching of the economical processing of the byproduct has been under way for a long time, but the industrial implementation of recovery technology, that is suitable in all aspects, has not yet been realized. The use of by-products, in addition to reduce the risk of contamination of environmental elements, may be useful for the recovery of valuable metals, which contained therein.